SERTIFIKASI HALAL PRODUKPANGAN SEBAGAI BENTUK PERLINDUNGAN KONSUMEN BERDASARKAN UNDANG – UNDANG NO 8 TAHUN 1999 TENTANG PERLINDUNGAN KONSUMEN - Iie Mansoer (Program Studi Magister Ilmu Hukum Universitas Islam Nusantara, 2015)
Indonesian citizens are about 250 million people and 87% of all are Muslims, or it is about 200 million people are Muslims. It is a verypotential marketfor regional or international trade. In this globalization era with the free trade, the good has transnational circulation, including food product. The food productedin Japan, China and other countries which has no halal regulation would be easily found in Indonesia and other parts of world with Muslim population. Halal is a sensitive issue thatshould be prioritized by officials. Getting halal label on food and drink is one of the consumer’s rights which isguaranteed by constitution. Considering this condition, halal assurance of a productis not only a focus of Muslims concern to consume food, medicine, cosmetics and other products, but also becoming a management system and production system from international trade. Therefore, Indonesia as the largest Muslim Country in the world needs to push itself not to be left in developing halal production management and system. Moreover, it is expected to be the leading pioneer to develop it. In order to increase the people awareness in consuming halal food, officials should facilitate the socialization activities/ seminars and or halal product promotion in Indonesia or foreign countries.